OP0035 When Does the Therapeutic Window of Opportunity in Rheumatoid Arthritis Close? A Study in Two Early RA Cohorts. (10th June 2014) - Van Nies, J.A.; Gaujoux-Viala, C.; Tsonaka, R.; Huizinga, T.W.; Fautrel, B.; van der Helm-van Mil, A.H.
Abstract : Background: Observational cohort studies and clinical trials have shown that early initiation of DMARD-therapy is associated with less disease persistency (a higher frequency of DMARD-free sustained remission). 1 It has been suggested that disease processes in the very early phase are less matured and therefore more susceptible to disease modifying treatment; this period is called the therapeutic window of opportunity. It has been suggested that this period encompasses the first three months of the disease but there are almost no data on the timelines. Objectives: We set out to increase the comprehension of the time when the window "closes". We therefore explored the symptom duration at treatment onset in relation to achieving DMARD free sustained remission in RA-patients included in two early arthritis cohorts. Methods: RA patients treated with conventional DMARDs that were included in the Leiden Early Arthritis Clinic and ESPOIR, were studied. In both cohorts symptom onset was defined as the first symptoms (either pain or swelling) as reported by the patient. The outcome, DMARD-free sustained remission, was defined as the absence of clinical arthritis after cessation of DMARDs for the entire follow-up period and for at least 1 year. In the Leiden EAC the maximal follow-up was 15 years, in ESPOIR 4 years. For each cohort time-dependent ROC-curves were constructed to define the optimum cut-off of symptom duration. Analyses were performed when RA was defined according to the 1987 or the 2010 criteria. In the Leiden EAC sub-analyses were performed in ACPA-positive and ACPA-negative RA. Results: In total, 157/864 (18%) of the Leiden EAC RA patients (1987 criteria) achieved remission within 15 years and 26/558 (5%) of the ESPOIR 1987-RA patients within 4 years of follow-up. In both cohorts patients were middle aged (mean 56.7±SD 15.6 and 50.9±11.9 years) and the majority were female subjects (66% and 77%) and ACPA positive (54% and 50%). In both cohorts the relation between symptom duration at treatment onset and DMARD-free sustained remission was not linear. The AUCs were all low (<0.62). The symptom duration after which the chance on DMARD-free sustained remission decreased was 14.1 (95%CI 11.6-15.4) weeks in the Leiden EAC and 15.3 (95%CI 10.7-28.0) weeks in ESPOIR. When analysing 2010 RA, the cut off was 14.7 weeks (12.7-19.7) in the Leiden EAC and 13.0 weeks (5.4-104) in ESPOIR. Furthermore, in ACPA-positive RA it was 14.6 (7.6-78.3) weeks and in ACPA negative RA 18.9 weeks (10.4-59.0). Conclusions: The association between symptom duration at treatment initiation and disease persistency is not linear. The present data imply that the window of opportunity starts to close 13-19 weeks after symptom onset. More detailed studies on this subject are needed. References: van Nies JA et al. What is the evidence for the presence of a therapeutic window of opportunity in rheumatoid arthritis? A systematic literature review. ARD 2013 [epub] Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5266